Computational Method to Analyze Novel Industrial-Type Compact Heat Exchangers Fin Designs - (:unkn) unknown (My University, 2022)
In this study, the computational fluid dynamics (CFD) method of numerical simulations has been applied to determine the heat load and pressure drop characteristics of computational method to analyze novel industrial-type compact heat exchangers fin designs. Two CFD software programs, Ansys Fluent and STAR-CCM+, were tested with air laminar flow. The research work demonstrated that Ansys Fluent is the more sensitive CFD software to laminar flow out of the two. Seven fin designs were tested to evaluate their performance in compact heat exchangers. The friction factor, f, and the Chilton Colburn factor, j, were used as the primary measures of performance. It was found that designs with the lower levels of velocity streamline disturbance, give lower friction factor while the highest Chilton Colburn factors, j, are produced by particular interactions between the fluid flow and the fin. As expected, for all the designs, the friction factor f decreases with an increase in Reynolds number while the plot of Chilton Colburn factor j increases by either no amount or a small amount with an increase in Reynolds number. It is was also found that a finer mesh size plays an important role the analysis of the thermophysical characteristics of the fin design. Finer mesh size result in more accuracy in the prediction of heat load and pressure drop results.